The practice of dance as extracurricular activity is related to higher motivation and physical activity level in students - Da Rosa A.F.* (2018)
© Edições Desafio Singular.The aim of the current study is to compare motivation, self-concept and physical activity level between students practicing dance as extracurricular activity and those who do not. The total of 200 students (mean age 8 ± 0.8 years) divided in two groups participated in the experiment: a) physical education (PE) and b) physical education combined with dance practices (PEDP). Two questionnaires were used, one for the parents (Schooling - Economic stratum) and one for students. The students’ questionnaire consisted of a structured interview divided in four parts: a) General information; b) Motivation; c) Self-concept; and d) Physical activity level. Descriptive and inferential statistics were used. Results showed that students in the PEDP group were more motivated by Status (p = 0.049) and General Affiliation (p = 0.010), whereas 88% of the students in the PE group showed higher social self-concept (p = 0.010). With respect to physical activity level, 100% (p = 0.000) of students in the PEDP group were active and showed screen time 3.88 hours per day (p = 0.000). It was possible concluding that students in the PEDP group showed higher motivation and physical activity level than those in the PE group, who showed better self-concept.